2021
DOI: 10.5005/jp-journals-10071-23856
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Respiratory and Hemodynamic Parameters of COVID-19 and Non-COVID-19 ARDS Patients

Abstract: A bstract Background COVID-19 can cause a clinical spectrum from asymptomatic disease to life-threatening respiratory failure and acute respiratory distress syndrome (ARDS). There is an ongoing discussion whether the clinical presentation and ventilatory parameters are the same as typical ARDS or not. There is no clear understanding of how the hemodynamic parameters have been affected in COVID-19 ARDS patients. We aimed to compare hemodynamic and respiratory parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 113 Finally, the recent COVID‐19 pandemic has brought to public attention the practice of proning patients with SARS‐CoV‐2 to improve respiratory function. 114 These dose‐response curves provide a reference from nonpathological subjects that can be used for clinical management purposes to assess expected hemodynamic and autonomic variation. This has applications in surgical cases such as Trendelenburg positioning or surgeries using spinal frames, along with tests of orthostatic response.…”
Section: Discussionmentioning
confidence: 99%
“… 113 Finally, the recent COVID‐19 pandemic has brought to public attention the practice of proning patients with SARS‐CoV‐2 to improve respiratory function. 114 These dose‐response curves provide a reference from nonpathological subjects that can be used for clinical management purposes to assess expected hemodynamic and autonomic variation. This has applications in surgical cases such as Trendelenburg positioning or surgeries using spinal frames, along with tests of orthostatic response.…”
Section: Discussionmentioning
confidence: 99%
“…This timing is consistent with previous research, both in the context of C-ARDS and non-C-ARDS patients, indicating that the therapeutic benefits of prone positioning tend to become more pronounced around the 5-7 day mark after intubation. [47][48][49] In summary, this study found that the novel saturation and oxygenation indices showed the strongest predictive value for ICU mortality on the third day of treatment. Particularly, OI-ΔP insp , OSI-ΔP insp , and OSI-MP dyn emerged as promising indicators for predicting clinical outcomes.…”
Section: Discussionmentioning
confidence: 57%
“…This timing is consistent with previous research, both in the context of C-ARDS and non-C-ARDS patients, indicating that the therapeutic benefits of prone positioning tend to become more pronounced around the 5-7 day mark after intubation. 47 49 …”
Section: Discussionmentioning
confidence: 99%
“…In Asar and colleagues’ 2021 study with 17 CARDS and 16 NCARDS patients, they examined the mean APACHE II values [ 8 ]. They found that the mean APACHE II value was 21 for both CARDS and NCARDS patients.…”
Section: Discussionmentioning
confidence: 99%